Singapore Shipping Trust. - Goh, Wei Qin. (2009)
This paper studies the development and performance of the three shipping trusts listed in Singapore. With the current Subprime crisis and downturn in the shipping industry, we analyse some of the real risks and impact facing each shipping trust, for instance, counterparty risks and financing issues. We also explore the shipping trusts’ financial performance through comparison with the Singapore market, as well as with Singapore REITs, Singapore shipping stocks and their foreign peers. Results from CAPM show presence of risk-adjusted returns for the equal-weighted shipping trust portfolio in the before-subprime period, indicating the attractiveness of shipping trusts during better economic conditions. However, Fama and French model shows negative alphas across all sample periods, suggesting the underperformance of shipping trusts since their debut. We observe low correlation of shipping trust returns with STI returns, which is indicative of shipping trust’s possible diversification benefits in an investor’s portfolio.